Propaganda Feminisme dan Perubahan Sosial - Tia Mutihah Umar (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2005)
Feminist movement was born as reaction toward discrimination, unfairness, and oppressiontoward women in social system. In principle, the movement viewed that the root cause of such problem could be traced back to state development policy eternalized by patriarchal family system and religious doctrines. Upon its socializations, feminist movement utilizes propaganda technique to construct their message in order to provide different communication effects. For over the years, despite pro-cons over feminism, the feminist movement has significantly changed the world’s social system as appear on some levels such as patterns of behavior and human interactions. A solution focused on ethical dimension of Human Development which being framed and reinterpreted in the manner of theological beliefs was needed to increase the result of feminist movement.